Discourse Phenomena as a Window to the Interfaces - Alba Cerrudo (Universitat Autònoma de Barcelona, 2019)
This paper examines the two lines of analysis that are generally pursued when dealing with discourse phenomena in the generative tradition: syntactico-centric and interface-based approaches. Syntactico-centric analyses are criticized because they need construction-specific mechanisms, while interface-based analyses sometimes challenge standard assumptions about the architecture of grammar. The discussion is mainly theoretical, but three case studies serve as exemplification: focalization, ellipsis and parentheticals. The second part of the paper is focused on parentheticals; a brief proposal is presented regarding the distinction between free and anchored parentheticals from a syntax-phonology interface perspective. The general conclusion is that following an interface-based perspective to approach discourse phenomena can help us gain new insights about the nature of the interfaces and their role in grammar.